2022
DOI: 10.1016/j.virusres.2022.198674
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a recurrent insertion in the N-terminal domain of the SARS-CoV-2 spike glycoprotein

Abstract: Tracking the evolution of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) through genomic surveillance programs is undoubtedly one of the key priorities in the current pandemic situation. Although the genome of SARS-CoV-2 acquires mutations at a slower rate compared with other RNA viruses, evolutionary pressures derived from the widespread circulation of SARS-CoV-2 in the human population have progressively favored the global emergence, though natural selection, of several variants of concern … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 90 publications
1
42
0
Order By: Relevance
“…Notably, a recent study has shown that this insertion is present also in seasonal coronaviruses HCoV-229E, thus leading to the hypothesis that it could have been acquired by template switching involving the genomes of HCoV-229E and SARS-CoV-2 in coinfected patients ( 5 ). Notably, a recent structure-based study has speculated that this insertion was not related to immune escape due to lack of overlap with known immune epitopes ( 43 ). No information on the functional role of this insertion is known so far.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a recent study has shown that this insertion is present also in seasonal coronaviruses HCoV-229E, thus leading to the hypothesis that it could have been acquired by template switching involving the genomes of HCoV-229E and SARS-CoV-2 in coinfected patients ( 5 ). Notably, a recent structure-based study has speculated that this insertion was not related to immune escape due to lack of overlap with known immune epitopes ( 43 ). No information on the functional role of this insertion is known so far.…”
Section: Resultsmentioning
confidence: 99%
“…The recurrent emergence of insertions (between R214 and D215) in the NTD, and their progressive increase in multiple lineages, including VOC have been recently documented. 54 It is important to note that many indel positions are highly variable due to independent/multiple origins of indels 27,53 and/or nearby substitutions that affect alignment. Indels have special relevance as they can fine-tune the 3D structure beyond point mutations and are known to occur in surface-exposed loops.…”
Section: Discussionmentioning
confidence: 99%
“…All resulting genomes were grouped based on the inserted nucleotide sequence, whose exact position and phase of insertion were defined based on the alignment with the reference SARS-CoV-2 genome sequence (Wuhan-Hu-1, NCBI accession ID: NC_045512.2) and a reference BA.2 genome (EPI_ISL_8128502). Following the nomenclature scheme proposed in our previous work (Gerdol et al, 2022), each of these groups was labeled with progressive Roman numerals, following their chronological order of identification, starting from insertion L.…”
Section: Methodsmentioning
confidence: 99%